Exclusión, empleo y tecnología de la información y comunicación - Fernández Villalta, José María (TRABAJO. Revista Iberoamericana de Relaciones Laborales, 2004)
En este Articulo se intentan realizar Propuestas a cerca de los procedimientos que se han de seguir para mejorar el acceso de los colectivos excluidos al conocimiento de las Tecnologías de la Información (TIC). En general se suele correr el riesgo de Planificar la Formación de los colectivos excluidos atendiendo a variables como el Genero, la edad o el Origen, se mantiene el prejuicio social derivado de la estadística de pensar que estos son indicadores que unifican a los individuos. Sin dejar de pensar que en algunos casos estas variables influyen a continuación intento demostrar que son variable económicas o de prestigio y nivel de bienestar u origen social, roles familiares, etc., los que van a determinar que los `desheredados’ accedan al bienestar. El uso de las TIC será por lo tanto una consecuencia de la Obtención de otros DERECHOS FUNDAMENTALES._____________________________In this Article the Author describes and analyse some proposals in relation with the procedures and actions necessaries to improve the access and usability of the ICT (Information and Communications Technologies) in the Social exclusion field. Fernández de Villalta, focus the problem in relation with the wrong use, of ’Classical Social Items’ as Gender; or Origin Country, etc to describe and define the hypo-" thesis and problems of The social exclusion and their relationship with Information, and Communications Technologies. This Wrong hypothesis, produce erroneous Actions and crucial problems in order to draw and define best practices oriented to improve the technologies skills and social labour integration of the excluding groups The Author of this article, propose to use other Social Analysis of exclusion, taking in account the influence of Economical and Psychosocial variables as: The prestige and political status, the level of education, Personal skills and family origins. The use of these items permit the creation of `news Social Categories’ to explain the exclusion situation and theirs consequences in this Global and social world. Finally Mrs Fernandez de Villalta believes that the knowledge and use of new Technologies is not only a tool to decrease the Social Exclusion. This factor is crucial and essential, in the fight for the recognition of the Social and Human rights.